Spear-Thrower or Bow? Refining Comparative Metrics to Track the Cultural Transmission of Bow Technology in the Andes - Marsh, Erik Johnson (2024)
The appearance of new projectile technology can be among the most significant shifts in a region’s history. To metrically distinguish dart and arrow projectile points, we present new data on hafted archaeological projectile points from museums in South America and compare them to published data from North America.We suggest that using oversized ethnographic arrows as comparative data can lead us to misidentify small dart points as arrows. We recommend building comparative baselines only with archaeological points, which better reflect the metric impact of points’ use-lives. Hence there seems to be no universally applicable comparative dataset or discriminant formula, but there are clear tendencies. We applied these to a database of lithic projectile points (n = 422) from 21 archaeological sites in the Andes (16°–37° S). We carefully graded point integrity to eliminate retouched or recycled points. In our database, the earliest arrow-sized points are from ~1800 cal BP in the Lake Titicaca Basin (16° S), later than previously suggested for the earliest Andean bows. Farther south in Mendoza (34°S), similarly sized points appear later, ~1300 cal BP. Over this part ofthe Andes, our data suggest a southward trajectory of bows, which quickly replaced spear-throwers.